Dispersive biofilm from membrane bioreactor strains: effects of diffusible signal factor addition and characterization by dispersion index - Song, Wonjung; Ryu, Junhee; Jung, Jaehyun; Yu, Youngjae; Choi, Suyoung; Kweon, Jihyang (Frontiers in Microbiology, 2023)
Biofilm occurs ubiquitously in water system. Excessive biofilm formation deteriorates severely system performance in several water and wastewater treatment processes. Quorum sensing systems were controlled in this study with a signal compound cis-2-Decenoic acid (CDA) to regulate various functions of microbial communities, including motility, enzyme production, and extracellular polymeric substance (EPS) production in biofilm. The addition of CDA to six strains extracted from membrane bioreactor sludge and the Pseudomonas aeruginosa PAO1 strain was examined for modulating biofilm development by regulating DSF expression. As the CDA doses increased, optical density of the biofilm dispersion assay increased, and the decrease in EPS of the biofilm was obvious on membrane surfaces. The three-dimensional visual images and quantitative analyses of biofilm formation with CDA proved thinner, less massive, and more dispersive than those without; to evaluate its dispersive intensity, a dispersion index was proposed. This could compare the dispersive effects of CDA dosing to other biofilms or efficiencies of biofouling control practices such as backwashing or new cleaning methods.